2010
DOI: 10.1128/jcm.00419-10
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and Genotypic Characterization of Group B Streptococcal Isolates in Southern Brazil

Abstract: One-hundred sixty-eight group B streptococcal (GBS) isolates from a Brazilian hospital were phenotypically and genotypically characterized. Isolates were recovered from human sources from April 2006 to May 2008 and classified as either invasive, noninvasive, or colonizing isolates. Classical methods for serotyping and antibiotic resistance profiling were employed. Clonal groups were also defined by pulsed-field gel electrophoresis (PFGE). Results showed that susceptibility to beta-lactam antimicrobials was pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
35
5
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(51 citation statements)
references
References 51 publications
10
35
5
1
Order By: Relevance
“…The same scenario was observed among neonatal (2/64 cases; 3%) for the years 2000 to 2004 [12] and non-pregnant adult infections (2/225 cases; 1%) from 2001 to 2008 [14]. After 2010, reports from Brazil Ireland and the US [15][16][17][18] revealed an increased prevalence of serotype IV in colonisation and infection, suggesting the possibility that this serotype could be emerging as an important pathogen, as happened with serotype V during the 1990s [19].…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…The same scenario was observed among neonatal (2/64 cases; 3%) for the years 2000 to 2004 [12] and non-pregnant adult infections (2/225 cases; 1%) from 2001 to 2008 [14]. After 2010, reports from Brazil Ireland and the US [15][16][17][18] revealed an increased prevalence of serotype IV in colonisation and infection, suggesting the possibility that this serotype could be emerging as an important pathogen, as happened with serotype V during the 1990s [19].…”
Section: Introductionmentioning
confidence: 55%
“…The sudden increase of GBS serotype IV detection in different countries does not rely on the emergence of type IV/CC17 only, as other genetic lineages (such as CC1 and CC23) or different types of pulsed-field gel electrophoresis have been identified, constituting the majority of the serotype IV isolates [15][16][17][18]20]. A careful surveillance of GBS type IV/ST291 emergence is recommended, in order to define its host specificity, tropism, virulence potential and antibiotic resistance phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…40,41 . Mais recentemente, em 2010, um estudo de Curitiba (PR) revelou os tipos Ia e Ib como os mais frequentes em doença de início precoce, e o IV na infecção tardia, com apenas sete casos descritos 42 . O que chama a atenção é que os sorotipos Ib e II, que predominaram na maioria dos estudos brasileiros, não são considerados de maior virulência.…”
Section: Discussionunclassified
“…To our knowledge, this proportion is the highest ever reported for serotype IV GBS adult invasive disease. While we did not characterize the GBS serotype distribution among colonized pregnant women (these studies are under way in our laboratories), others have observed increasing numbers of serotype IV strains among colonizing isolates (17,18,(38)(39)(40). Studies aimed at developing a capsular polysaccharide antigen-based GBS vaccine are ongoing worldwide, with several formulations that do not include serotype IV already under clinical trials (41).…”
Section: Discussionmentioning
confidence: 99%